Recycling and environmental awareness in improving the sustainability of the planet - Calle Aguilar, Ilda Ruth (2016)
This research is about a recycling program in enhancing environmental awareness in the fifth grade students of primary education. This program allows children to be aware of the importance of the separation, collection and treatment of waste as essential step for recycling and consequently improve the sustainability of our planet. The overall objective was to determine the influence of a recycling program in the improvement of environmental awareness in students in the fifth grade of primary education of the Educational Institution No. 10018 of the district of Santa Rosa- 2015. The theoretical foundations that guided this research was made in the theories: Ecological Bronfenbrenner and the moral development ofKohlberg, which leads to explain the problem from the scientific point ofview. In addition, the methodological :framework supports it, where the hypothesis that allowed determining if the recycling program influences significantly on improving environmental awareness. It is experimental type of design quasi-experimental. The techniques and instruments used for this purpose were: observation and questionnaire to measure the level of environmental awareness.